The level of Critical thinking of Mathematical students in Faculty of Education - Sana'a University - Al-Usofi, Bushra Abdalaleem; Al-baqeri, Dhekra Mohammed (Journal of Educational and Psychological Sciences, 2023)
This current study aimed to identify the level of Critical thinking for students of mathematics at Faculty of Education in Sana'a University. The descriptive survey method was used to achieve the objectives of the study. The California Critical Thinking Skills Test (CCTST), which was translated by Nufal and Marei (2000), was applied by the researcher on (170) students of both male and female, The applied test involved five skills which are Analysis, Inference, Induction, Deduction and Evaluation. The test was adapted to suit the Yemeni environment. It was investigated to be valid and reliable. The results of the study indicated that the overall critical thinking level and its sub-skills of mathematics students were low and there were no differences based on academic levels (first, second, third, fourth). Furthermore, the result approve that there was no relation among the levels of critical thinking and the average of general school certificate.
Keywords: Critical thinking; Critical thinking skill